The Effect of Experimentally Induced Vitamin E and Selenium Deficiency on Erythrocytes Osmotic Fragility and Phagocytosis in Pregnant Awassi Ewes and Their Newborn Lamb: The Effect of Experimentally Induced Vitamin E and Selenium Deficiency on Erythrocytes Osmotic Fragility and Phagocytosis in Pregnant Awassi Ewes and Their Newborn Lamb - H. Judi, A. M. (The Iraqi Journal of Veterinary Medicine, 2013)
Experimental induction of vitamin E and selenium deficiency using deficient diet was carried out on fourteen pregnant Awassi ewes and their newborn lambs to study the effect of the deficiency on erythrocytes osmotic fragility and phagocytosis. From the fourteen deficient ewes, seven were vaccinated with Rev I vaccine and seven ewes as control group, and their newborn lambs were used in the study. Results were showed increased in the concentration of saline solution in start and complete erythrocyte hemolysis in deficient lambs (0.52 ± 0.01 and 0.54 ± 0.01) and (0.42 ± 0.01 and 0.44 ± 0.00) respectively and in deficient ewes (0.53 ± 0.01 and 0.54 ± 0.01) and (0.43 ± 0.01 and 0.44 ± 0.00) respectively. Results showed a low phagocytic index in deficient lambs (9.40 ± 0.87 and 10.60 ± 1.16) and in deficient ewes (12.14 ± 0.85 and 12.42 ± 0.75) compared to phagocytic index in control lambs (43.85±0.91) and in control ewes (43.14 ±0.91).